3D simulations of strongly magnetized non-rotating supernovae: explosion dynamics and remnant properties. Issue 3 (11th November 2022) - Varma, Vishnu; Müller, Bernhard; Schneider, Fabian R N
ABSTRACT: We investigate the impact of strong initial magnetic fields in core-collapse supernovae of non-rotating progenitors by simulating the collapse and explosion of a $16.9\, M_\odot$ star for a strong- and weak-field case assuming a twisted-torus field with initial central field strengths of ${≈ }10^{12}$ and ${≈ }10^{6}\, G$ . The strong-field model has been set up with a view to the fossil-field scenario for magnetar formation and emulates a pre-collapse field configuration that may occur in massive stars formed by a merger. This model undergoes shock revival already $100\, ms$ after bounce and reaches an explosion energy of $9.3× 10^{50}\, erg$ at $310\, ms$, in contrast to a more delayed and less energetic explosion in the weak-field model. The strong magnetic fields help trigger a neutrino-driven explosion early on, which results in a rapid rise and saturation of the explosion energy. Dynamically, the strong initial field leads to a fast build-up of magnetic fields in the gain region to 40 per cent of kinetic equipartition and also creates sizable pre-shock ram pressure perturbations that are known to be conducive to asymmetric shock expansion. For the strong-field model, we find an extrapolated neutron star kick of ${≈ }350\, km\, s^{-1}$, a spin period of ${≈ }70\, ms$, and no spin-kick alignment. The dipole field strength of the proto-neutron star is $2× 10^{14}\, G$ by the end of the simulation with a declining trend. Surprisingly, the surface dipole field in the weak-field model is stronger, which argues against a straightforward connection between pre-collapse fields and the birth magnetic fields of neutron stars.